Exploring Winter Trends of Urban Heat Island Phenomena in Kathmandu Valley - Gupta, Priyanka; Bajracharya, Ashim Ratna (Journal of Engineering Issues and Solutions, 2025)
The Urban Heat Island (UHI) effect presents a growing environmental concern for the Kathmandu Valley, significantly shaping microclimates and impacting local energy consumption. While much of the existing research emphasizes summer UHI conditions, the phenomenon’s behaviour during winter months remains relatively underexamined. The study investigates the influence of surface materials & albedo characteristics on temperature variations across different urban and suburban zones during winter. A mixed-method approach was adopted, combining field survey and spatial analysis of building albedo properties with secondary temperature data. Primary data captured details on surface types and albedo value, while secondary data from the Department of Hydrology and Meteorology (DHM) provided 10 years of temperature records, focusing specifically on December. Through trend analysis of maximum and minimum temperatures, subtle yet consistent differences in urban and suburban microclimates were observed. Trend analysis was done using Mann kendall slope and Sen’s slope test, while the building materials were categorized and their albedo properties and its impact was studied. Results show that although winter UHI intensity is relatively low compared to summer, urban zones still exhibit slightly elevated temperatures. This is primarily attributed to dense built-up areas, limited vegetative cover, and dominance of impervious surfaces like concrete and asphalt, which retain heat and hinder night-time cooling. Conversely, areas with traditional or mixed typologies—characterized by breathable materials, open courtyards, and permeable surfaces— exhibit lower UHI intensity during winter. The long-term trend analysis indicates a gradual warming of urban cores over the past decade, even during winter months, suggesting that urbanization is subtly shifting seasonal thermal patterns.